Meningkatkan Kreativitas Siswa dengan Memanfaatkan Barang Bekas pada Mata Pelajaran Seni Budaya dan Prakarya - Aditya, Rama; Muhajirin, Muhammad; Ihwan, Ihwan (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to increase the creativity of grade IV students at Sdit Al-Maarif Darussalam for the 2024/2025 academic year. This research was carried out at Sdit Al-Maarif Darussalam with a total of 10 children consisting of 6 boys and 4 girls. This study uses classroom action research techniques (PTK The research subjects are 10 children. The object of this research uses data collection techniques, observation, documentation and tests. The data analysis techniques used are qualitative and quantitative techniques The research can be said to be successful if it has reached a score or criterion of 80. The results of the research conducted showed that the increase in creativity of pre-action and pre-cycle students only reached 40%, in the first cycle increased to 60% and in the second cycle increased to 90%. So it can be concluded that the selection of learning methods is very important in arousing students' creativity because if the learning methods presented are interesting will make students more focused and pay attention to the learning conveyed by the teacher, especially in learning cultural arts which is considered difficult by most students because it requires students to apply their imagination. The research was stopped in cycle II because it had met the success criteria.